Impact of Benzodiazepines and Illness Duration on Obsessive–Compulsive Disorder during COVID-19 in Italy: Exploring Symptoms’ Evolutionary Benefits - Giordano D’Urso; Alfonso Magliacano; Marco Manzo; Mattia Vittorio Pomes; Carla Iuliano; Felice Iasevoli; Bernardo Dell’Osso; Andrea de Bartolomeis (Brain Sciences, 2024)
Obsessive–compulsive disorder (OCD) is believed to follow a waxing and waning course, often according to environmental stressors. During the COVID-19 pandemic, pre-existing OCD symptoms were reported to increase and to change from checking to washing behaviors, while new-onset symptoms were predominantly of the hoarding type. In the present study, we followed the evolution of OCD symptoms, anxiety, depression, and insights of illness in forty-six OCD patients throughout the pandemic. Clinical measures were collected at four different time points before and during the COVID-19 pandemic in Italy. Within-subject comparisons were used to compare clinical scale scores across time, and correlations were examined between patients’ baseline characteristics and changes in clinical scores. We found that all clinical measures increased during the first Italian lockdown with respect to the pre-pandemic values. Anxiety decreased during the temporary elimination of restriction provisions, whereas the severity of OCD symptoms and insight returned to pre-pandemic values during the second mandatory lockdown. These results were observed only in two sub-groups of patients: those taking benzodiazepines and those with shorter illness duration. Our findings suggest the need for additional clinical attention to these specific sub-groups of OCD patients in case of particularly distressing circumstances while pointing to a possible adaptive role of their OCD symptoms when the environment requires a higher care of hygiene and an extraordinary supply of essential resources.